Suppression of PtrDUF579-3 Expression Causes Structural Changes of the Glucuronoxylan in Populus - Song, Dongliang; Gui, Jinshan; Liu, Chenchen; Sun, Jiayan; Li, Laigeng (Frontiers in Plant Science, 2016)
DUF579 (domain unknown function 579) genes have been reported to play diverse roles in cell wall biosynthesis, such as in glucuronoxylan (GX) synthesis. As GX is a major type of hemicelluloses in hard wood species, how DUF579 genes function in wood formation remains to be demonstrated in planta. This study reports a Populus DUF579 gene, PtrDUF579-3, which is characterized for its function in wood cell wall formation. PtrDUF579-3 is localized in Golgi apparatus and catalyzes methylation of the glucuronic acid (GlcA) in GX biosynthesis. Suppression of PtrDUF579-3 expression in Populus caused a reduction in both the GlcA side chain number and GlcA side chain methylation on the GX backbone. The modified GX polymer through PtrDUF579-3 suppression was more susceptible to acid treatment and the PtrDUF579-3 suppressed plants displayed enhanced cellulose digestibility. These results suggest that PtrDUF579-3 is involved in GX biosynthesis and GX structure can be modified through PtrDUF579-3 suppression in Populus.